Analisis faktor Risiko Kejadian Filariasis di Dusun Tanjung Bayur Desa Sungai Asam Kecamatan Sungai Raya Kabupaten Pontianak. - Anshari, Rudi; Suhartono, Suhartono; Setiani, Onny (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2004)
ABSTRACT Background : Filariasis is a contagious disease that caused by Fillaria parasite and is flued by mosquito bite. Indonesia has 23 mosquito species such as Monsonia, Anopheles, Culex, Aedes, and Armigeres genus which are potential vectors of elephantiasis. 2,5 billion people at risk with elephantiasis cases in the world. Indonesia has 6.233 Fillariasis chronic cases, West Kalimantan has 156 chronic cases (MF Rate 4,5 %). In Tanjung Bayur Orchard was found 17 cases 13 chronic cases (MF Rate 17,8 %) and in 4 mortality case. Tanjung Bayur is a marsh area with field , ditch, water plant which can be prepared as growing vector place. The objective is to determine the risk factors that influence fillariasis in Tanjung Bayur orchard, Sungai Asam Village. Methods : this research used case control design or retrospective study with 13 cases and 27 control. Risk factor that include in this research were vector species, vector density, ditch, water plant, marsh, rice field, pool, underbrush, livestock cage, clothes hanging, temperature, dampness, lighting, existence of gauze at ventilation, wall construction, existence livestock in a home, habit to use curtain, habit to use remedy agains gnats, habit to stay out of the house in the night. Research location has done at Tanjung Bayur Orchard on Sungai Asam Village, District of Sungai Raya. Data analysis use univariat technique, bivariat analysis with Chi-Square Test and multivariate analysis with Logistic Regression Test. Results: Research result, shows that existence ditch variable (OR = 8,0 ; 95 % CI = 1,5 - 43,4), existence water plant variable (OR = 4,6; 95 % Cl = 1,1 – 44,9) and habit to use curtain (OR = 0,04; 95 % Cl = 0,006 – 0,23) is meaningful for fillariasis infection. Conclusions : existence of water plant (OR = 4,6; 95 % Cl = 1,1 – 18,7), is risk factor that the most dominant for fillariasis infection. Suggestion, the regular illumination from health worker for people to give information about environmental and fillariasis dangerous. Key word: Risk factor, fillariasis water plant, kinds Sungai asam village